1997
DOI: 10.1111/j.1365-2214.1997.tb00966.x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of behavioural and emotional problems in deaf children and adolescents: comparison of two rating scales

Abstract: The aim of this study was to establish rates of behavioural and emotional problems, and of social maladjustment, in a population of deaf children, particularly in relation to different methods of communication. The parents of 84 children who attended two schools for the deaf took part. They completed the parents' checklist (PCL), a behaviour rating scale for deaf children, and the Child Behaviour Checklist (CBCL), a measure widely used in the general population. The two instruments were significantly correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
1
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 23 publications
3
63
1
2
Order By: Relevance
“…All studies were published in peerreviewed journals and were assessed for their level of evidence. In line with the guidelines of the Cochrane Collaboration, 19 the included studies had recommendation B (cohort or case-control study), except for 1 study by Vostanis et al 7 that had recommendation C (caseseries study). Because of differences in outcomes when examining different study samples, the 18 included studies on specific psychopathological symptoms were grouped based on the study sample and recapitulated in Table 1 (community-based samples), Table 2 (samples with children attending special schools and/or profoundly HI children), and …”
Section: Selection Of Articlesmentioning
confidence: 95%
“…All studies were published in peerreviewed journals and were assessed for their level of evidence. In line with the guidelines of the Cochrane Collaboration, 19 the included studies had recommendation B (cohort or case-control study), except for 1 study by Vostanis et al 7 that had recommendation C (caseseries study). Because of differences in outcomes when examining different study samples, the 18 included studies on specific psychopathological symptoms were grouped based on the study sample and recapitulated in Table 1 (community-based samples), Table 2 (samples with children attending special schools and/or profoundly HI children), and …”
Section: Selection Of Articlesmentioning
confidence: 95%
“…Hindley 1997;Van Eldik 2004) show a higher incidence and prevalence of mental health problems in deaf children compared with their hearing counterparts. Specifically, emotional and behavioural problems seem to be twice as common among deaf children (Vostanis 1997). Neurodevelopmental disorders appear to have a different prevalence: the incidence of ADHD in children with inherited deafness is the same as in their hearing counterparts but higher than in children with non-inherited deafness (Hindley 1998).…”
Section: In Most Cases the Gene Is Recessivementioning
confidence: 99%
“…Within the literature on behavioural and emotional problems in hearing impaired children, the reported rates of psychiatric disorders are wide ranging. Using a London sample, Hindley et al [1994] reported that 43-50.3% of children with hearing impairments had behavioural problems or psychiatric disorders compared to 40-77% reported by Vostantis et al [1997] using a Birmingham sample. The London Health Observatory [2001] reported the prevalence of mild behavioural disorders in hearing children to be 15,000/100,000, moderate disorders to be 7,000/100,000 and severe disorders to be 1,850/100,000.…”
Section: Introductionmentioning
confidence: 99%